Strategi Kepala Madrasah dalam Membentuk Siswa Berprestasi di MTsS Lubuk Kilangan (Tazakka: Jurnal Pendidikan dan Keislaman, 2024)
This research aims to obtain the madrasa head's strategy and the supporting and inhibiting factors in forming outstanding students at MTsS Lubuk Kilangan in various aspects. The research method used is qualitative with a case study approach. Data was collected through interviews, observation and documentation studies. The main respondents involved madrasa heads, teachers, outstanding students, and students' parents. Data analysis was carried out using content analysis techniques to identify main patterns and themes related to the madrasa head's strategy. The research results showed that the madrasa head at MTsS Lubuk Kilangan had implemented various strategies to improve student achievement. There are general and specific strategies. Apart from that, the supporting factors for the strategy are cooperation between the madrasah community, complete facilities from the madrasah, and the use of educational technology used by the madrasah. Meanwhile, the inhibiting factors are limited time, lack of expert teaching staff and motivation. students at MTsS Lubuk Kilangan
Keywords: Student Achievement; Madrasah Head Strategy; MTsS Lubuk Kilangan